Genetic testing of sperm donors in China: a survey of current practices - Huang, Chuan; Wang, Qi-Lin; Wu, Hui-Lan; Huang, Zeng-Hui; Zhang, Xin-Zong; Zhu, Wen-Bing (Frontiers in Endocrinology, 2023)
The National Health and Family Planning Commission of China (NHFPCC) issued the "Measures for the Management of Human Sperm Banks," which was revised in 2003 and is still in effect today. One of the standard guidelines is that potential donors undergo laboratory testing to exclude infectious and genetic diseases and karyotype analysis. However, patient demands for donor genetic testing have also increased, and only karyotype analysis to exclude genetic diseases is not sufficient to meet these demands.Objective：To examine donor genetic screening practices at sperm banks in China and to evaluate the qualifications and skills of genetic counselors at the banks.An electronic survey was distributed to twenty-seven sperm banks to examine donor genetic screening practices at sperm banks in China and to evaluate the qualifications and skills of genetic counselors at the banks. Twenty-six human sperm banks responded to a 32-question survey about their current practices related to genetic testing of sperm donors.The 26 sperm banks reported that all qualified sperm donors undergo karyotype analysis; 22 banks (84.6%) collected three generations of family history from each qualified sperm donor; 10 (38.5%) reported that they attempted to accommodate special requests from donor semen recipients for particular genetic tests. Only 2 of the 26 (7.7%) sperm banks reported that they performed whole-exome sequencing. At all the sperm banks, consent for genetic testing was obtained as part of the overall contract for sperm donors. Nineteen (73.1%) sperm banks had genetic counselors on their staff, while six (23.1%) had no genetic counselors on their staff but had access to genetic counselors at the hospital. Only one (3.8%) sperm bank had no genetic counselors on their staff or at the hospital.The need for larger scale genetic testing of donors and recipients and an extensive panel of genetic tests specific to the Chinese population. Additionally, professionally trained geneticists must be employed as genetic counsellors so that the results of genetic tests and their implications can be explained to donors.